Prediction model for the initial seed clearing angles of a precision seedmeter based on vector fields - Wan, Jiao; Zhang, Junjie; Chen, Xuhui; Shen, Hao; Huang, Yuxiang; Shi, Jiangtao (International Journal of Agricultural and Biological Engineering, 2024)
Seed clearing is a critical stage during precision seed metering process to ensure high seed singulation. However,there is a lack of understanding of the dynamics in the seed clearing process. In this study, a model was developed to predictinitial seed clearing angle, in the seed clearing process using vector fields. The model was applied to an existing high-speedmetering device and soybean seeds, and the model was evaluated with bench testing results. Results showed that dynamicchanges in forces and constraints of seeds during the seed clearing process could be abstracted as vectors, and the changes ofvector directions could be described by their phase angles. The phase angles were functions of the rotational angle of the seedmeter. The phase angle of the constraint boundary linearly increases with the increase of the rotational angle. The phase angleof the force fluctuates, as the rotational angle changes. Initial seed clearing angle obtained from the phase angles varies from 8°to 59°, depending on the seeder travel speed. When comparing the values of the initial seed clearing angles predicted by themodel with those from the bench tests, the root mean square error (RMSE) were from 2.73 to 3.14, and the correlation (r)between predict and observer were all higher than 0.98, indicating that the model had reasonably good accuracy. Keywords: mechanical precision seeder, initial seed clearing angle, prediction model, vector fields, high-speed photographytechnology DOI: 10.25165/j.ijabe.20241702.7029 Citation: Jiao W, Zhang J J, Chen X H, Shen H, Huang Y X, Shi J T. Prediction model for the initial seed clearing angles of aprecision seed meter based on vector fields. Int J Agric & Biol Eng, 2024; 17(2): 140–148